Two new species and one new combination of Helina Robineau-Desvoidy, 1830 (Diptera: Muscidae) from China - Wang, Ming-Fu; Sun, Chen; Wang, Rong-Rong (Entomologica Fennica, 2012)
Two new species of the genus Helina Robineau-Desvoidy, 1830 from Sichuan, China are described and illustrated, i.e. Helina fulvibasicosta Ming-Fu Wang sp. n. and Helina flavipes Ming-Fu Wang&Chen Sun sp. n. After re-examining the holotype, Helina occidentalisinica Feng, Shi & Li, 2005 is transferred to the genus Hebecnema Schnabl.